The Routledge companion to interdisciplinary studies in singing. - Helga R. Gudmundsdottir; Beynon, Carol; Ludke, Karen; Cohen, Annabel J., 1947- (Routledge, 2022)
"Interdisciplinary Studies in Singing, Volumes I, II and III are dedicated to the three themes of Development, Education, and Well-being in attempting to define the current state of theory and research in the field of singing. The Advancing Interdisciplinary Research in Singing (AIRS) Major Collaborative Research Initiative has gathered researchers from across the globe to collaborate and improve our understanding. The approach is unique in considering the entire lifespan, from infancy to later life. It also recognizes the diversity of singing styles and the role of singing in different cultures. Cutting-edge research shows in great depth how people throughout the world learn to sing, and demonstrates benefits of singing from both educational and well-being standpoints, Volume II - Singing and Education is sub-divided into three interdisciplinary sub-themes on singing representing the research sub-themes of the AIRS project, namely: 1) Learning to sing naturally, 2) Formal teaching of singing, and 3) Teaching through singing It begins with a foundational chapter, explaining basic issues and concepts associated with each sub-theme, followed by chapterss that range from the obvious field of music to psychology, education, sociology, computer science, linguistics, physiology, and neuroscience among others. Co-editors provide a concluding chapter that synthesizes key points from the chapters in the book, represents an advance beyond the introduction, and offers a new theoretical perspective as well as take-home messages for public policy in education, community development, and health"--